Associations between molecular biomarkers and MR-based cartilage composition and knee joint morphology: data from the Osteoarthritis Initiative. Issue 8 (August 2018) - Joseph, G.B.; Nevitt, M.C.; McCulloch, C.E.; Neumann, J.; Lynch, J.A.; Heilmeier, U.; Lane, N.E.; Link, T.M.
Summary: Objective: The purpose of this study was to assess the associations between serum/urine biomarkers for osteoarthritis and magnetic resonance (MR) imaging measures of cartilage composition and joint structure (cartilage, meniscus, and bone marrow), using MR imaging data from the Osteoarthritis Initiative (OAI). Design: 141 subjects with Kellgren Lawrence (KL) grades 0–3 in the right knee and with available serum/urine biomarker assays were selected from the OAI. Cartilage magnetic resonance imaging (MRI) T2 measurements were performed in the medial femur, lateral femur, medial tibia, lateral tibia, and patella compartments. Compartment-specific knee morphologic grading [whole-organ magnetic resonance imaging score (WORMS)] in the cartilage, meniscus, and bone marrow was also performed. We focused on associations of serum hyaluronan (sHA), serum cartilage oligomeric matrix protein (sCOMP), serum matrix metalloproteinase-3 (sMMP3), and Urine Carboxy-Terminal Telepeptides of Type II Collagen (uCtX-II)) with MRI parameters (T2, WORMS), assessed using partial correlations adjusted for age, gender, body mass index (BMI), KL grade in both knees, and diabetes status. Results: Higher levels of sHA, sMMP3 and sCOMP were correlated ( P < 0.05) with T2 of the lateral femur ( r = 0.18 to 0.32) and lateral tibia ( r = 0.17 to 0.23), and with average T2 of all knee regions ( r = 0.23). uCTXII was correlated with patellar T2 ( r = 0.19, P = 0.04). Among the morphologic measures, sHA and sMMP3 was positively correlated ( r = 0.17 to 0.21, P < 0.05) with meniscal damage. Conclusions: This study suggests weak, but statistically significant, correlations between serum biomarkers of OA (sHA, sCOMP, and sMMP3) and MRI T2 measures of cartilage extra-cellular matrix degeneration.